Genetic Information: Consumers' Right to Privacy Versus Insurance Companies' Right to Know a Public Opinion Survey - Borna, Shaheen (Journal of business ethics, 1999)
In this paper we present arguments for and against the disclosure of genetic information to the insurance companies. One of the main issues which emerges from these arguments is the question of who should be responsible for the health insurance costs of the individuals who are most likely to be affected by the disclosure of genetic information. The results of a resident opinion survey related to the above question are presented and public policy alternatives related to the survey findings are discussed at the end of this paper.